Penguatan Pendidikan Karakter Religius Peserta Didik Melalui Kegiatan Ekstrakulikuler ROHIS di SMP Negeri 5 Purworejo - Saudah, Siti (LPPM IAINU Kebumen, 2023)
This research aims to describe the Rohis extracurricular activity program in improving students' character education, efforts to foster students' religious character through Rohis extracurricular activities, supporting and inhibiting factors for Rohis activities in developing students' character education at SMP Negeri 5 Purworejo. This research uses a qualitative approach with analytical descriptive methods. The research subjects were school heads, teachers, employees and students. Data collection techniques in this research used interviews, observation and documentation. Data analysis uses the Miles and Huberman model, namely data reduction, data presentation, and drawing conclusions. The results of this research show that Spiritual Extracurricular Activities at SMP Negeri 5 Purworejo are proven to be able to strengthen students' religious character education by implementing activity programs: (1) Cultivating 5S (Greetings, Smiles, Greetings, Politeness, Manners); (2) Clean Friday; (3) Commemoration of Islamic Holidays (PHBI); (4) BTQ (Reading and Writing the Qur'an); (5) Religious Bands, Hadroh, Marawis and Nasyid; (6) Spiritual Tourism & Natural Tadabur; (7) Duha and Dzhur prayers in school; and (8) Filling the wall with Islamic themes. After spiritual activities are held, students have an awareness of good character which can be proven by carrying out activities with religious nuances such as reading the Qur’an, imtaq guidance, and midday midday prayers in congregation, being able to implement an attitude of tolerance between religions and so on.